Struggle Values in Main Characters in The Climbers Film: Sosiology of Literature Review 《攀登者》电影中主角奋斗的价值观：文学社会分析 - Dinda Anindya Putri; Intan Erwani (Sinolingua: Journal of Chinese Studies, 2023)
This research discusses the struggle values of the main characters in The Climbers film. The purpose of this research is to describe the struggle values of the main character in The Climbers film. This research is based on Joyomartono's theory of struggle values to find out the struggle values shown by the characters in The Climbers film. The theoretical basis used in this research is the sociology of literary theory. The method used in this research is descriptive qualitative. The data collection method used is the listening and note-taking technique. The data analysis method used is interactive model introduce by Miles Huberman and Saldana techniques, namely data collection, data presentation, condensation and, conclusion.  Based on the analysis of The Climbers film, the struggle values contained in this film include four components, namely, the value of self-sacrifice, the value of cooperation, the value of unyielding spirit and the value of helping each other. Thus, it can be concluded that film proves to contain social interaction and struggle values, which can be seen in the attitude or manner of the character Fāng wǔzhōu（方五洲）.